Oligopolio e incertidumbre sobre la demanda: una revisión - López, Jesús (Estudios de Economía, 2016)
The purpose of this paper is to carry out a review of the academic literature oninformation exchange agreements about demand in oligopolistic models andthe derivation of some political consequences with respect to the effectivenessand limits of these agreements. The main problem is in knowing how and towhat extend these agreements affect the welfare of producers, consumers andsociety as a whole. At a glance there are several factors involved: The type ofcompetition (price versus quantities), the nature of uncertainty (private versuscommon), the nature of goods (substitutive versus complementary) and thenumber of firms.